PENERAPAN MODEL PEMBELAJARAN BERBASIS PERMAINAN TERHADAP PENINGKATAN KEAKTIFAN PADA MATERI KEBUGARAN JASMANI SISWA KELAS V SDN BARENG 1 KOTA MALANG - Viva Lenia Davina Permata; Dudung Ma’ruf Nuris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to enhance the engagement of fifth-grade elementary school students in physical fitness lessons through the implementation of a game-based learning model. The study employed Classroom Action Research (CAR) methodology conducted over two cycles, each comprising planning, implementation, observation, and reflection stages. The subjects were 38 fifth-grade students (18 boys and 20 girls) at SDN Bareng 1, Malang City. Data were collected using observation sheets and questionnaires to measure student engagement levels during the learning process. The results indicate that the game-based learning model successfully increased student engagement. Initial observations showed an engagement level of 44% (low category), which rose to 79% by the second meeting of Cycle I (moderate category), and further increased to 83% and 86% in Cycle II (good category). This improvement occurred because game-based learning fostered a more active, interactive, and enjoyable learning environment through various physical games. Thus, it can be concluded that the game-based learning model is effective in enhancing student engagement in physical education at the elementary school level.